Profile Of The Use Of The Drug In Patients Acute Respiratory Tract Infection In Child Patients Aged 5-10 Years: Profil Penggunaan Obat Pada Pasien Infeksi Saluran Nafas Akut (ISPA) Pada Pasien Anak Usia 5-10 Tahun - irma novrianti, Irma (Jurnal FARMASIMED (JFM), 2025)
Acute respiratory tract infection  is a disease that is often experienced by toddlers and children caused by bacterial, viral infections, without or accompanied by lung parenchyma. The purpose of this study was to determine the therapy used in ARI patients at the Puskesmas "X" in Tarakan City in the period January-July 2023. This study was experimental with a descriptive method. Sampling was carried out using simple random sampling with a retrospective approach in the period January-July 2023. The research data were grouped and analyzed descriptively and presented in the form of tables and percentages. Based on the results of the study, the most widely used treatments in prescriptions were mucolytics (98.2%), antihistamines (95.7%) and analgesics-antipyretics (70.6%) and the least were antiasthma (4.0%), antibiotics (1.8%) and Corticosteroids (1.2%). The most widely used types of drugs in prescriptions are ambroxol (98.2%), CTM (95.7%), and paracetamol (69.7%) and the least used are Dexamethasone (1.2%), ibuprofen 200 mg (0.9%), and vitamins (12.8%). It can be concluded that the most widely used drug in the treatment of ARI is mucolytic drugs (ambroxol) and the least used drug is corticosteroids, example dexamethasone.